Eardrums : Literary Modernism as Sonic Warfare. - Whitney, Tyler (Northwestern University Press, 2019)
"In this innovative study, Tyler Whitney demonstrates how a transformation and militarization of the civilian soundscape in the late nineteenth and early twentieth centuries left indelible traces on the literature that defined the period. Both formally and thematically, the modernist aesthetics of Franz Kafka, Robert Musil, Detlev von Liliencron, and Peter Altenberg drew on this blurring of martial and civilian soundscapes in traumatic and performative repetitions of war. At the same time, Richard Huelsenbeck assaulted audiences in Zurich with his "sound poems," which combined references to World War I, colonialism, and violent encounters in urban spaces with nonsensical utterances and linguistic detritus--all accompanied by the relentless beating of a drum on the stage of the Cabaret Voltaire. "Eardrums" is the first book-length study to explore the relationship between acoustical modernity and German modernism, charting a literary and cultural history written in and around the eardrum. The result is not only a new way of understanding the sonic impulses behind key literary texts from the period. It also outlines an entirely new approach to the study of literature as as the interaction of text and sonic practice, voice and noise, which will be of interest to scholars across literary studies, media theory, sound studies, and the history of science"--Provided by publisher.